2021
DOI: 10.1177/23259671211044993
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Initial Stability of Oblong, Large Circular, and Multiple-Plug “Snowman” Osteochondral Autografts for Elongated Focal Cartilage Lesions: A Biomechanical Study in a Porcine Model

Abstract: Background: Distal femoral osteochondral allograft transplantation (OAT) is an effective treatment of osteochondral lesions in the knee measuring >2 cm2 in select patients. Prior studies have demonstrated that the morphology of the plug can affect graft-host interference fit. To our knowledge, there are no data comparing the initial biomechanical stability of standard cylindrical plugs with multiple-plug and oblong-plug morphologies. Hypothesis: Large cylindrical single-plug (LCSP) and oblong single-plug (O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…There is limited biomechanical evidence to compare single-plug and multiple-plug OCA transplantation for the treatment of HSLs. A biomechanical study in a porcine model by Dwivedi et al 5 demonstrated that there was no significant difference in pull-out strength and displacement in maximum load between the large cylindrical single plug and multiple plugs OCA transplantation. Results from their study showed good initial stability for the multiple plugs OCA; however, further in vivo study is needed to validate stability, healing process, and clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…There is limited biomechanical evidence to compare single-plug and multiple-plug OCA transplantation for the treatment of HSLs. A biomechanical study in a porcine model by Dwivedi et al 5 demonstrated that there was no significant difference in pull-out strength and displacement in maximum load between the large cylindrical single plug and multiple plugs OCA transplantation. Results from their study showed good initial stability for the multiple plugs OCA; however, further in vivo study is needed to validate stability, healing process, and clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Resistance to pull-out and push-in forces is higher in press-fit cylindrical single-plug grafts that are greater in diameter and depth and are "bottomed out." 54,62,63 For these grafts, larger diameter, thinner, perfect-depth grafts are more likely to resist subsidence. 63,64 Depths less than 7 mm are at greater risk for displacement and subsequent biomechanical failure, while greater depths are associated with biological failure mechanisms.…”
Section: Impacts Of Transplantation Methods On Osteochondral Allograf...mentioning
confidence: 99%
“…7 For autografts and allografts, using multiple plugs to treat a single articular defect is discouraged based on reduced graft stability, decreased ability to resist axial loading, poor restoration of articular surface contour, and inferior interface healing and integration. 13,54,56 Emerging techniques that include instrumentation to fabricate elliptical OCAs that may allow for a single graft to be used to treat defects that might otherwise require multiple overlapping plugs may be advantageous. 18 However, fabrication requires impacting the graft, indications are limited by graft size, shape, and anatomic locations, and early failures have been reported.…”
Section: Impacts Of Transplantation Methods On Osteochondral Allograf...mentioning
confidence: 99%
See 1 more Smart Citation
“…Prior biomechanical studies have demonstrated short plugs (< 4 mm) have significantly less pull-out strength than longer plugs of > 7 mm, and another study showed no difference between 7 mm and 10 mm plugs [10,11]. BioUni® provides approximately 10 mm of bone restoration at its maximum depth, which allows it to have significantly more bone centrally when compared to the two plugs used in the snowman configuration [12,13]. Prior studies have evaluated the outcomes of multiplug OCA transplantation (snowman technique) and demonstrated improvement in post-operative outcome measures but inferior results to single graft transplant utilizing a dowel technique [14].…”
Section: Introductionmentioning
confidence: 99%